(untitled) (Indian Journal of Animal Production and Management, 2024)
A study was carried out to find out the effect of housing on serum biochemical parameters of Nellore Jodipi lambs under tropical environmental conditions. Thirty weaned Nellore ram lambs of 3-4 months age were selected based on body weight and randomly divided into three groups of ten animals each. Temperature and humidity values were significantly (P<0.05) different among all the groups. The mean serum biochemical parameters like creatinine, urea, sodium, potassium, calcium, ALT and AST were significantly (P<0.05) higher in group II (1.75±1.00 mg/dl, 21.23±1.00 mg/dl, 150.16±1.00 mmol/L, 4.76±0.22 mmol/L, 12.87±1.00 mg/dl, 243.38±1.00 IU/L, 32.03±1.00I U/L) when compared to group I (1.36±1.00 mg/dl, 13.71±1.00 mg/dl, 144.95±1.0 mmol/L, 4.55±0.22 mmol/L, 12.06±1.00 mg/dl, 171.77±1.00 IU/L, 26.93±1.00 IU/L) and group III (1.32±1.00 mg/dl, 8.96±1.00 mg/dl, 141.77±1.00 mmol/L, 3.99±1.00 mmol/L, 11.27±1.00 mg/dl, 124.53±1.00 IU/L, 23.88±1.00 IU/L) respectively, whereas, other parameters like glucose was significantly (P<0.05) lower in group II (39.07±1.00 mg/dl) when compared to group I (55.41±1.00 mg/dl) and III (75.26±1.00 mg/dl). It was concluded that the housing system of elevated slatted flooring with galvalume roofing proved to be effective in controlling heat stress and maintaining normal serum biochemical parameters of Nellore ram lambs.